Mobile Device Management for the Use of Bring Your Own Device (BYOD) as Company Data Security during the Covid-19 Pandemic - Yolanda Mega Puspita; Muhaimin Hasanudin (IJISTECH (International Journal of Information System and Technology), 2022)
Since the end of 2019 a large outbreak has hit almost the entire world, namely the Covid-19 pandemic. COVID-19 has encouraged millions of employees to change their jobs from coming to the office to working at home. This phenomenon is known as Bring Your Own Device (BYOD).  Good policies and guidelines on the use of BYOD must be followed to prevent some form of security breach and maintain user privacy, confidentiality, integrity, and availability of organisational data, and the same security on the devices of employees who use their own devices to process company data.  To solve these problems, researchers implemented Mobile Device Management with VMware workspace one uem tools to monitor, control and protect mobile devices. The system uses Windows server. The results of the research can be input to the company to secure and monitor company data on employee work devices.